IMPLEMENTASI STRATEGI INOVATIF MANAJEMEN SUMBER DAYA MANUSIA DALAM ADAPTASI TERHADAP ERA DIGITAL (STUDI KASUS PT. MITRA TATA KERJA) - Putri Kareena Nugis; Diah Ayu Sanggarwati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
In the face of the ever-expanding digital era, technological adaptation emerges as pivotal for companies seeking to maintain competitiveness and operational efficiency. This research examines the implementation of innovative human resource management (HR) strategies within PT. Work Management Partners to adapt to the digital era. Data were gathered through in-depth interviews, participant observation, surveys, and document analysis. The findings indicate that the company has effectively integrated digitalization into recruitment processes, utilized Learning Management Systems (LMS), and implemented digital-based performance evaluations. These initiatives have notably enhanced operational efficiency, bolstered employee engagement, and fortified the company's competitive edge. Nonetheless, the research identifies challenges such as resistance to change and limitations in technological infrastructure. Recommendations for companies include prioritizing effective change management, investing in technological infrastructure, providing continuous training for employees, integrating digital systems, and enhancing communication and transparency. By implementing these recommendations, PT. Work Management Partners can further enhance their ability to navigate the digital era and cultivate an inclusive and innovative work environment for their employees.